2011
DOI: 10.1080/10401334.2011.561755
|View full text |Cite
|
Sign up to set email alerts
|

Core Practical Objectives: A Means to Standardize the 4th-Year Emergency Medicine Clerkship

Abstract: CPOs were successfully integrated into an EM clerkship. Preliminary data suggest that CPO guidelines can be used to standardize EM clerkships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…With these learning missions, interns would be able to learn with clear aims during clinical learning. [24] In addition, clinical teachers, officers of departments and the internship teaching affairs office can also make their evaluation for interns. With the teachers’ assessments and self-assessments, interns learn about their weaknesses, adjust their learning state and improve themselves in real time, which drive the interns to be continuously positive and enthusiastic.…”
Section: Discussionmentioning
confidence: 99%
“…With these learning missions, interns would be able to learn with clear aims during clinical learning. [24] In addition, clinical teachers, officers of departments and the internship teaching affairs office can also make their evaluation for interns. With the teachers’ assessments and self-assessments, interns learn about their weaknesses, adjust their learning state and improve themselves in real time, which drive the interns to be continuously positive and enthusiastic.…”
Section: Discussionmentioning
confidence: 99%
“…One study found a positive correlation between student completion of core practical objective guidelines (such as number of patient encounters) and postrotation examination scores as well as clerkship grades (8). Even though there have been multiple attempts to standardize the curriculum through the use of consensus guidelines, few use an evidence-based approach toward formalizing educational strategies (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…. 그 후 학생인턴의 역할 변화와 현황에 대한 연구 (Marracino et al, 1998) 와 함께 이들에게 무엇을 어디까지 교육할 것인가에 대한 전국적인 합의를 위해 학생인턴교육에서 가장 중요한 위치를 차지하고 있는 내과를 중심으로 연구가 이루어졌고 (Green et al, 2002;Green et al, 2004;Sidlow, 2001;Sidlow et al, 2002), 학생인턴이 전공과목 선 택에 어떠한 역할을 하는지에 대한 연구가 학생인턴교육과 관련 있 는 전공에서 연구되었으며 (Azizzadeh et al, 2003;Coates et al, 2003;Hueston et al, 2004), 이의 개선을 위한 지속적인 연구가 있다 (Aiyer et al, 2008;Coates et al, 2003;Lampe et al, 2008;Lindeman et al, 2013;Lyss-lerman et al, 2009;Woodland et al, 2011).…”
unclassified